2020
DOI: 10.1038/s41598-020-66816-x
|View full text |Cite
|
Sign up to set email alerts
|

Omentin: a biomarker of cardiovascular risk in individuals with axial spondyloarthritis

Abstract: Cardiovascular (CV) disease is the main cause of mortality in axial spondyloarthritis (axSpA). CV risk is enhanced by dysregulation of adipokines. Low omentin levels were associated with metabolic dysfunction and CV disease in conditions different from axSpA. Accordingly, we evaluated the genetic and functional implication of omentin in CV risk and subclinical atherosclerosis in a cohort of 385 axSpA patients. Subclinical atherosclerosis was evaluated by carotid ultrasound. Omentin rs12409609, in linkage diseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…These data support a potential role of omentin as a cardiovascular risk biomarker in axSpA. 130 …”
Section: Omentinsupporting
confidence: 72%
“…These data support a potential role of omentin as a cardiovascular risk biomarker in axSpA. 130 …”
Section: Omentinsupporting
confidence: 72%
“…In previous studies of our group, we assessed the potential role of different molecules as biomarkers of CV risk in axSpA. The results obtained in those studies supported the implication of such molecules in the high CV risk observed in axSpA patients [ 4 , 10 , 11 ]. This led us to search for other molecules that may also be biomarkers of CV risk in axSpA.…”
Section: Introductionsupporting
confidence: 58%
“…Data on sex, age, body mass index, blood pressure, total cholesterol, high-density lipoprotein (HDL)-cholesterol, low-density lipoprotein (LDL)-cholesterol and triglycerides at the time of study, as well as history of traditional CV risk factors (smoking, obesity, dyslipidemia, and hypertension) were collected. Obesity, dyslipidemia, and hypertension were defined as previously described [ 4 ]. In particular, obesity was defined if body mass index (calculated as weight in kilograms divided by height in squared meters) was ≥30.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is in line with our study in Asian Indians, where circulating adiponectin levels serve as a mediator in conferring the genetic risk of cardiometabolic diseases. A previous study in a Spanish population has shown a significant association of the minor allele of the omentin SNP rs12409609, which is in complete LD with SNP rs2274907, with low omentin gene expression [52]. Given the positive correlation between plasma omentin and adiponectin levels [12, 3537], it is possible that low omentin expression might contribute to the reduction in adiponectin levels, which, in turn, could possibly increase the cardiometabolic risk among ‘A’ allele carriers.…”
Section: Discussionmentioning
confidence: 99%